Optimized well configuration of gas-assisted gravity drainage process. Issue 1 (2nd January 2016) - Cho, Jinhyung; Jeong, Moon Sik; Lee, Kun Sang
Abstract : CO2 flooding has been widespread as one of the effective enhanced oil recovery methods by oil swelling and viscosity reduction. In spite of the efficiencies, the improvement of oil recovery falls short of expectation, especially for immiscible flooding because unswept zone by injected CO2 still exists at the bottom of the reservoir owing to gravity overriding phenomenon. Gas-assisted gravity drainage (GAGD) has been applied to use CO2 gravity overriding conversely and improve carbon capture sequestration efficiency. During GAGD, the area of swept zone by injected CO2 is affected greatly by injector length and producer well perforation design. The producer well perforation just below the injectors inhales CO2 downwardly, which interrupts gas spread from the top. Moreover, CO2 out of the injector far away from the top is affected by the downward pull of the producer more than buoyancy to the top; so, gas does not spread throughout the wide range of the area. The unswept zone existed below the injectors at the end of production can be solved by new perforations in the producer under the injectors. Results obtained would give not only the strength of GAGD but also a suggestion for an effective well length and perforation design of GAGD process.